2023
DOI: 10.1161/atvbaha.122.318119
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Inheritance of Familial Hypercholesterolemia Gene Mutation Predisposes to Coronary Atherosclerosis as Assessed by Calcium Score in Adulthood

Abstract: Background: Animal studies have demonstrated that fetal exposure to high maternal cholesterol levels during pregnancy predisposes to aortic atheroma in the offspring. In humans, little is known about the consequences of this exposure on the development of atherosclerotic cardiovascular disease later in life. We wanted to assess whether maternal/paternal inheritance of familial hypercholesterolemia (FH) gene mutation could be associated with subclinical coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…In a multivariate analysis of the French National Registry of FH, it was shown that maternal inheritance of the FH gene is associated with an increase in CAC scores by 86% (95% CI, 23–170%; P = 0.003), a 1.81-fold higher risk of having a CAC score ≥ 100 Agatston units (95% CI, 1.06–3.11; P = 0.03), and a 2.72-fold risk of having a CAC score ≥ 400 Agatston units (95% CI, 1.39–5.51; P = 0.004) compared with paternal inheritance. 99 Given the apparent safety of statins in pregnancy, Graham and Raal 100 have recommended that women homozygous for FH or with a defined atherosclerotic vessel or aortic disease be treated with statins during pregnancy if lipoprotein apheresis is not a therapeutic option.…”
Section: Disparities In Cardiovascular Care For Women Whether Pregnan...mentioning
confidence: 99%
“…In a multivariate analysis of the French National Registry of FH, it was shown that maternal inheritance of the FH gene is associated with an increase in CAC scores by 86% (95% CI, 23–170%; P = 0.003), a 1.81-fold higher risk of having a CAC score ≥ 100 Agatston units (95% CI, 1.06–3.11; P = 0.03), and a 2.72-fold risk of having a CAC score ≥ 400 Agatston units (95% CI, 1.39–5.51; P = 0.004) compared with paternal inheritance. 99 Given the apparent safety of statins in pregnancy, Graham and Raal 100 have recommended that women homozygous for FH or with a defined atherosclerotic vessel or aortic disease be treated with statins during pregnancy if lipoprotein apheresis is not a therapeutic option.…”
Section: Disparities In Cardiovascular Care For Women Whether Pregnan...mentioning
confidence: 99%
“…On the other hand, a significant association between maternal inheritance and increased coronary artery calcium scores was observed in 1350 French patients, but no difference in prevalence of cardiovascular events [ 48 ▪ ]. Surprisingly, a Canadian study found a younger age at first event and a 1.5-fold increased risk of ASCVD adjusted for confounders with paternal inheritance compared to maternal inheritance [ 49 ].…”
Section: Dyslipidemia During Pregnancy: Consequences For the Offspringmentioning
confidence: 99%
“…Схожие данные были получены в другом ретроспективном исследовании с участием более чем 1300 пациентов, занесенных во французский регистр семейной гиперхолестеринемии. Пациенты с материнским наследованием дефектного гена семейной гиперхолестеринемии реже имели семейный анамнез преждевременных сердечно-сосудистых событий [30]. Механизмы, лежащие в основе данного феномена, неизвестны [29].…”
Section: вопросы современной педиатрииunclassified